Up on the Second Floor - Mike Yoder (Symphony in the Flint Hills, 2019)
Introduction: Flint Hills communities have their humor, lies, and legends of the main street, just as early humans saw the same in the stars. One of those main street legends is expressed in this song by Mike Yoder of the Alferd Packer Memorial String Band.